“Sharing Is Caring:” Australian Self-Trackers' Concepts and Practices of Personal Data Sharing and Privacy - Lupton, Deborah (Frontiers in Digital Health, 2021)
Self-tracking technologies and practices offer ways of generating vast reams of personal details, raising questions about how these data are revealed or exposed to others. In this article, I report on findings from an interview-based study of long-term Australian self-trackers who were collecting and reviewing personal information about their bodies and other aspects of their everyday lives. The discussion focuses on the participants' understandings and practices related to sharing their personal data and to data privacy. The contextual elements of self-tracked sharing and privacy concerns were evident in the participants' accounts and were strongly related to ideas about why and how these details should be accessed by others. Sharing personal information from self-tracking was largely viewed as an intimate social experience. The value of self-tracked data to contribute to close face-to-face relationships was recognized and related aspects of social privacy were identified. However, most participants did not consider the possibilities that their personal information could be distributed well-beyond these relationships by third parties for commercial purposes (or what has been termed “institutional privacy”). These findings contribute to a more-than-digital approach to personal data sharing and privacy practices that recognizes the interplay between digital and non-digital practices and contexts. They also highlight the relational and social dimensions of self-tracking and concepts of data privacy.